O movimento negro e o processo de elaboração das diretrizes curriculares nacionais para a educação das relações étnico-raciais - GATINHO, Andrio Alves (2008)
This research locates in the study field on curricul um and it turns about the performance of the black movement in the process of elaboration of the National Curricul um Guidelines for the Education of the Ethnic -racial Relations (NCGEERR), one of the actions promoted by the Brazilian government due to the c urrent political curricular adopted by the State. The methodological approach of this research is qualitative and had as techniques of collection of information, the documental research and application of questionnaires to the former - counselors, members of the commission responsible for the resolution 03/2004 from the National Board of Education (that founded the Guidelines) and to the militant s of the black movement that participated in the process of elaboration of N CGEERR. The sending of the questionnaires to the black militants was made by the internet through the sending to the discussion groups about the racial relationships and education and to an electronic addresses list of entities of the black movement of the whole Brazil. The answer s of the questionnaires were sent from militant representatives of groups and entities of the movement, that have experience in the expressive militancy and in their activities, they are teachers and develop projects about the racial subject in the school. The results of the research, show that the black movement was an important actor in the process of elaboration of the curriculum guidelines, and had participated actively, presenting general proposal and strengthen ing historical propositions. The black movement performance was important for the Guidelines elaboration, because politically demarcated the space and the proposals from the movement. I defend that when we make a positive evaluation of the NCGEERR, the black movement ca n not analyze the ideological strategy of identities under formation, in curriculum politics that are part of these guidelines.